When Does Family Ownership Promote Proactive Environmental Strategy? The Role of the Firm’s Long-Term Orientation - Dou, Junsheng (Journal of business ethics, 2019)
This research proposes an explanation for the conflicting extant evidence about whether family ownership of a business promotes proactive environmental strategy (PES). Based on insights drawn from strategic reference point theory, organizational identity theory, and the socioemotional wealth preservation perspective, we propose that family ownership has a moderated–mediated relationship with PES, with commitment as a moderator and long-term orientation as a mediator. A test using 454 China private firms with different levels of family ownership supports the hypotheses. This shows that PES as a strategy related to business ethics does not happen without commitment and long-term orientation.